2021
DOI: 10.1001/jamadermatol.2021.0469
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features, Prognostic Factors, and Treatment Interventions for Ulceration in Patients With Infantile Hemangioma

Abstract: IMPORTANCEUlceration is a common complication of infantile hemangioma (IH), which leads to substantial morbidity. Ulceration in IH has not been systematically studied since the advent of β-blocker therapy for IH. OBJECTIVESTo examine treatment interventions used for ulceration in IH and identify clinical prognostic indicators of healing time. DESIGN, SETTING, AND PARTICIPANTS A retrospective, multicenter cohort study was conducted on 436 consecutive patients with a clinical diagnosis of ulcerated IH and availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 17 publications
1
27
0
1
Order By: Relevance
“…In a 2013 study evaluating propranolol use to treat IH in PHACE syndrome, three patients showed similar worsening ulceration of IH, 10 as described here. Recently, Fernandez Faith et al's multicenter retrospective cohort study found that lower‐dose propranolol therapy (<1 mg/kg/day) demonstrated a trend to faster healing time of ulcerated IH compared with standard propranolol doses 15 . Of note, in their findings, a fifth of ulcerated IHs developed after active treatment (including, but not limited to propranolol).…”
Section: Discussionmentioning
confidence: 98%
“…In a 2013 study evaluating propranolol use to treat IH in PHACE syndrome, three patients showed similar worsening ulceration of IH, 10 as described here. Recently, Fernandez Faith et al's multicenter retrospective cohort study found that lower‐dose propranolol therapy (<1 mg/kg/day) demonstrated a trend to faster healing time of ulcerated IH compared with standard propranolol doses 15 . Of note, in their findings, a fifth of ulcerated IHs developed after active treatment (including, but not limited to propranolol).…”
Section: Discussionmentioning
confidence: 98%
“…The previously mentioned European expert consensus group recommended dosage starting at 1 mg/kg/day in either inpatient or outpatient settings, 28 increasing to a goal dosage of 2–3 mg/kg/day if required 25 . A recent study has found lower doses of propranolol ≤1 mg/kg/day have been associated with shorter healing times 21 …”
Section: Discussionmentioning
confidence: 99%
“…Beta-blockers (e.g., propranolol ointment, timolol cream, etc .) 182 , glucocorticoids, bleomycin, rapamycin, and other antitumor drugs can be employed.…”
Section: The Applications Of Nanocarrier- or Mn-based Transdermal Del...mentioning
confidence: 99%